Who do you trust while bubbles grow and blow? A comparative analysis of the explanatory power of accounting and patent information for the market values of German firms - Markus Reitzig; Fred Ramb (Deutsche Bundesbank, 2004)
We present a theoretical and empirical analysis of the fitness of national German (German Commercial Code - Handelsgesetzbuch (HGB)) and international (IAS and US-GAAP) accounting information, as well as European patent data to explain the market values of German manufacturing firms. For the chosen volatile period from 1997 to 2002, cautious national accounting information does not correlate with the firms? residual market values (RMV). International accounting information makes no meaningful contribution to explaining firms? RMV and seems to measure overinvestment only. Finally, patents counted at the individual country level correlate with the firms? RMV.
Keywords: D82; M40; M41; K11; 330; Accounting standards; investor information; market value; patents; Unternehmenswert; Marktwert; Verarbeitendes Gewerbe; Börsenkurs; Jahresabschluss; Informationswert; Patent; Schätzung; Deutschland